John E. JOSEPH. Language and Identity: National, Ethnic, Religious: Palgrave, 2004. 268 pp. ISBN 0-333-99752-2 - Barbosa, Joaquim (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2017)
.